2019
DOI: 10.1002/ejic.201801477
|View full text |Cite
|
Sign up to set email alerts
|

NHC Nickel Catalyzed Hiyama‐ and Negishi‐Type Cross‐Coupling of Aryl Fluorides and Investigations on the Stability of Nickel(II) Fluoroaryl Alkyl Complexes

Abstract: The reactivity of [Ni(iPr2Im)4(µ‐COD)] 1 (iPr2Im = 1,3‐diisopropyl‐imidazolin‐2‐ylidene, COD = 1,4‐cyclooctadiene) in Hiyama‐ and Negishi‐type cross‐coupling reactions as well as the synthesis of several novel nickel fluoroaryl alkyl complexes is reported. Hiyama coupling of 1.1 equiv. perfluoroaromatics and 1 equiv. PhSi(OR)3 (R = Me, Et) with 5 mol‐% of 1 as catalyst leads to the C–C coupling product ArF–Ph in good to fair yields. In presence of the additive NMe4F alkoxy transfer from PhSi(OR)3 to the perflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…1.952(2) Å), they differ significantly in the trans isomer 2a- cis (Ni–C­(NHC) 1.905 Å vs Ni–C­(neosilyl) 2.032 Å). These metric values are in good agreement with other structurally characterized Ni-NHC complexes ,, and can be attributed to the different trans-influence of alkyl and NHC ligands, respectively.…”
Section: Resultssupporting
confidence: 80%
“…1.952(2) Å), they differ significantly in the trans isomer 2a- cis (Ni–C­(NHC) 1.905 Å vs Ni–C­(neosilyl) 2.032 Å). These metric values are in good agreement with other structurally characterized Ni-NHC complexes ,, and can be attributed to the different trans-influence of alkyl and NHC ligands, respectively.…”
Section: Resultssupporting
confidence: 80%
“…Both complexes adopt in the solid state square planar geometries for which the nickel atom is coordinated with two NHC and two alkyl ligands in a trans ‐configuration. The bonding parameter are unexceptional, the Ni–C bond lengths to the NHC ligand ( 9 : 1.879(2) Å, 11 : 1.887(3) Å) are close to those of other trans ‐[Ni II (NHC) 2 X 2 ] complexes, and the bond lengths Ni–C to the alkyl ligand ( 9 : 2.006(2) Å, 11 : 2.017(3) Å) are in the expected range. In comparison to Danopoulos' cis ‐configured complex cis ‐[Ni( i Pr 2 Im Me ) 2 (CH 3 ) 2 ][4d] are the Ni–C distances to the NHC carbene carbon atoms of 1.8790(16) Å in 9 slightly shorter (in cis ‐[Ni( i Pr 2 Im Me ) 2 (CH 3 ) 2 ]: 1.930(2) Å, 1.910(2) Å) and the Ni–CH 3 distances of 2.0060(15) Å slightly longer (in cis ‐[Ni( i Pr 2 Im Me ) 2 (CH 3 ) 2 ]: 1.966(2) Å, 1.975(3) Å).…”
Section: Resultsmentioning
confidence: 60%
“…We reported recently on the reactivity of the dinuclear complex [{Ni( i Pr 2 Im) 2 } 2 ( µ ‐(η 2 :η 2 )‐COD)] ( i Pr 2 Im = 1,3‐diisopropyl‐imidazolin‐2‐ylidene, COD = 1,4‐cyclooctadiene) in Hiyama‐ and Negishi‐type cross‐coupling reactions as well as on the synthesis of several novel nickel fluoroaryl alkyl complexes . We demonstrated that the nickel‐catalyzed Negishi cross‐coupling of C 6 F 6 or C 7 F 8 and zinc diorganyl reagents [ZnR 2 ] (R = Me, Et) leads only in traces to the desired product Ar F ‐R, although the corresponding nickel alkyl complexes are readily formed from the reaction of trans ‐[Ni( i Pr 2 Im) 2 (F)(Ar F )] with [ZnR 2 ] (R = Me, Et), as exemplified by the synthesis and characterization of a series of complexes trans ‐[Ni( i Pr 2 Im) 2 (R)(Ar F )] (R = CH 3 , Ar F = C 6 F 5 , C 7 F 7 , C 12 F 9 ; R = C 2 H 5 , Ar F = C 6 F 5 , C 7 F 7 , C 12 F 9 ) . We also have shown that these nickel alkyl complexes are stable even at elevated temperatures in solution for several days with respect to reductive elimination.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the formation of nickel alkyl complexes trans ‐[Ni( i Pr 2 Im) 2 (alkyl)(ArF)] (alkyl=Me, Et) 43 , which do not undergo controlled reductive elimination even at high temperature (Scheme 22). [67] …”
Section: Organic Transformations‐catalytic Processmentioning
confidence: 99%